Innovative Marketing in a Competitive Economy - Azimovna, Musayeva Shoira (Research Parks Publishing LLC, 2021)
This article discusses the introduction and widespread distribution of new products, services, technological processes are becoming the main factors in the growth of production, employment, investment, foreign trade turnover. It is here that the most significant reserves for improving product quality, saving labor and material costs, increasing labor productivity, improving the organization of production and increasing its efficiency are hidden. This predetermines the competitiveness of enterprises and their products in the domestic and world markets.